EFEKTIVITAS KULTUR Chaetoceros sp. SEBAGAI PAKAN ALAMI KERANG MUTIARA: PERBANDINGAN METODE LABORATORIUM DAN LAPANGAN - Fitrah Putra Amnur; Mukhlis, Alis; Damai Diniariwisan (Journal of Fish Nutrition, 2025)
Chaetoceros sp. is an important microalga in aquaculture that requires culture system optimization to enhance productivity and production efficiency. This study aimed to analyze the growth dynamics of Chaetoceros sp. in laboratory and outdoor culture systems and evaluate growth parameters and water quality factors affecting culture productivity. The study employed a completely randomized design with two treatments: laboratory culture (environmental control) and outdoor culture (natural conditions). Parameters observed included population density, relative growth, specific growth rate, doubling time, and water quality parameters (temperature, pH, salinity, light intensity) over 4 days of cultivation. Laboratory culture demonstrated superior performance with maximum population density of 3.60 × 10⁶ cells/ml, relative growth of 105.7 ± 12.27, specific growth rate of 19.7 ± 1.8%, and doubling time of 3.88 ± 0.34 days. Outdoor culture yielded maximum density of 3.28 × 10⁶ cells/ml, relative growth of 87.1 ± 12.44, specific growth rate of 16.9 ± 2.0%, and doubling time of 4.49 ± 0.51 days. Both methods achieved optimal exponential phase on day 3. Water quality parameters showed better stability in laboratory culture with lower variability. Strict environmental control in laboratory culture can reduce growth variability and improve predictability of Chaetoceros sp. culture results. Although laboratory culture is more technically efficient, outdoor culture remains viable for community applications considering cost efficiency and environmental sustainability.